Hydrogen sulfide in posthemorrhagic shock mesenteric lymph drainage alleviates kidney injury in rats - Han,B. (2015)
Posthemorrhagic shock mesenteric lymph (PHSML) is a key factor in multiple organ injury following hemorrhagic shock. We investigated the role of hydrogen sulfide (H2S) in PHSML drainage in alleviating acute kidney injury (AKI) by administering D,L-propargylglycine (PPG) and sodium hydrosulfide hydrate (NaHS) to 12 specific pathogen-free male Wistar rats with PHSML drainage. A hemorrhagic shock model was established in 4 experimental groups: shock, shock+drainage, shock+drainage+PPG (45 mg/kg, 0.5 h prehemorrhage), and shock+drainage+NaHS (28 µmol/kg, 0.5 h prehemorrhage). Fluid resuscitation was performed after 1 h of hypotension, and PHMSL was drained in the last three groups for 3 h after resuscitation. Renal function and histomorphology were assessed along with levels of H2S, cystathionine-γ-lyase (CSE), Toll-like receptor 4 (TLR4), interleukin (IL)-10, IL-12, and tumor necrosis factor (TNF)-α in renal tissue. Hemorrhagic shock induced AKI with increased urea and creatinine levels in plasma and higher H2S, CSE, TLR4, IL-10, IL-12, and TNF-α levels in renal tissue. PHSML drainage significantly reduced urea, creatinine, H2S, CSE, and TNF-α but not TLR4, IL-10, or IL-12. PPG decreased creatinine, H2S, IL-10, and TNF-α levels, but this effect was reversed by NaHS administration. In conclusion, PHSML drainage alleviated AKI following hemorrhagic shock by preventing increases in H2S and H2S-mediated inflammation.